The chicken-and-egg problem in the European Union Digital Markets Act - Fiona Scott Morton (Bruegel, 2024)
The gatekeeper platforms regulated by the European Union's Digital Markets Act (DMA) must comply with the law as of 6 March 2024. The DMA requires that core platform services create and make available interfaces that allow business users to access end users via the platform at lower cost and on better terms. For example, app developers will have the right to distribute on handsets through different app stores, using different payment services, directing users to purchase content on the web and charging different prices in different channels. The gatekeeper must provide the application programming interfaces, or APIs, to enable business users to take advantage of these rights. However, the DMA does not define exactly what those APIs should be. Rather, the law requires a gatekeeper's interface to be "effective," meaning business users can use it to enter, compete and innovate. Because such a design is not, in general, in the interest of the gatekeeper, the input of business users to both gatekeepers and the European Commission is critical for evaluating compliance with the law. Thus far there is little evidence of platforms interacting with business users or putting out interfaces for evaluation by business users, or of business users offering comments on what interfaces would be best for entry and competition. It may be that the interface must come first, and then its existence will stimulate entry of new business users or investment into new services that will use the interface. Rather like the chicken and the egg, which should come first? Business users are needed to help create useful interfaces, while useful interfaces are needed to justify investment and entry by business users.
Keywords: 330